Zakat, Legal Pluralism, and Revenue Governance in Kenya - Lyla Latif (Indonesian Journal for Islamic Studies, 2026)
Background: Neither African public finance studies nor Islamic fiscal studies have examined the administration of zakat in Kenya or the potential impact of domestic resource mobilization on public health financing to any significant extent.Objectives: This study examines how modern zakat governance has been shaped by the historical interplay between Islamic fiscal standards, the Omani government, British colonial rule, and Kenya’s post-independence constitutional framework. This study differs from previous research in that it provides the first empirical and phenomenological analysis of zakat governance in Kenya. It combines the concept of historical legal pluralism with original field evidence to assess whether state-administered zakat is an effective source of funding for public health.Methods: Interpretive Phenomenological Analysis (IPA) was used in conjunction with discursive analysis in this study. Qualitative data were collected from 166 participants in Mombasa and Nairobi, including 107 zakat payers, 42 Islamic scholars and religious leaders, and 17 policymakers and non-Muslim stakeholders. The data were organized into eight analytical themes. Result: The results show that Kenya’s zakat governance is legally pluralistic; among the 166 participants, trust, authority, legality, and consent emerged as key themes. Nearly all Muslims oppose government-administered zakat because they are concerned about corruption, constitutional obstacles, and the importance of preserving Islamic legal authority.Conclusion: This study proposes “conditional consent” as a legally and institutionally viable framework that can be used to reconcile the principles of Islamic finance with Kenya’s constitutional structure. It will expand the theoretical discourse on domestic resource mobilization and legal pluralism.